2003
DOI: 10.1215/s1522851702000236
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 trial of local chemotherapy with biodegradable carmustine (BCNU) wafers (Gliadel wafers) in patients with primary malignant glioma

Abstract: A previous placebo-controlled trial has shown that biodegradable 1,3-bis (2-chloroethyl)-1-nitrosourea (BCNU) wafers (Gliadel wafers) prolong survival in patients with recurrent glioblastoma multiforme. A previously completed phase 3 trial, also placebo controlled, in 32 patients with newly diagnosed malignant glioma also demonstrated a survival benefit in those patients treated with BCNU wafers. Because of the small number of patients in that trial, a larger phase 3 trial was performed to confirm these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
277
2
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(293 citation statements)
references
References 19 publications
4
277
2
10
Order By: Relevance
“…Biodegradable controlled-release polymers loaded with carmustine have been established as a safe and effective therapy for patients with malignant gliomas (8)(9)(10)(11)(12). Given the inherent advantages of locally-delivered chemotherapy, there has been continued interest in the development of additional controlled-release drug delivery systems suitable for intraparenchymal administration of novel antineoplastic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable controlled-release polymers loaded with carmustine have been established as a safe and effective therapy for patients with malignant gliomas (8)(9)(10)(11)(12). Given the inherent advantages of locally-delivered chemotherapy, there has been continued interest in the development of additional controlled-release drug delivery systems suitable for intraparenchymal administration of novel antineoplastic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of biodegradable polymers that release chemotherapeutic agents directly into the tumor has proved to be a promising strategy at increasing the local delivery of the drug. Nitrosoureas, including BCNU, are a class of chemotherapeutic agents that have been incorporated into biodegradable polymers and, upon intracranial implantation, have demonstrated efficacy in phase III clinical trials in patients with both recurrent and newly diagnosed malignant gliomas [3,36,40]. Importantly, in contrast to systemic administration of nitrosoureas, this treatment has not been associated with systemic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since most gliomas recur within 2 cm of the original tumor site [14,18], this anti-tumor strategy has the potential to control both local recurrence and improve overall survival. This approach has been evaluated in Phase III clinical trials with the nitrosourea, carmustine (BCNU) and has demonstrated significant improvement in survival in patients with malignant gliomas both at recurrence and at initial presentation [3,36,40].…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced MRI with Gd-DTPA (gadolium-diethylenetriamine pentaacetic acid) was used for monitoring the tumor size at different periods in the same animal and for comparison of the development of tumors in different groups of rats. The performance of MRI has been previously described (12). Whenever the rats died naturally or were sacrificed at one of the various time points, their brains were removed.…”
Section: Radiolabeling and Biodistribution Of Nanoparticles By Singlementioning
confidence: 99%
“…The Gliadels ® wafer, another intracavitary treatment using a controlled release system, has also been developed (10). The therapeutic effect of the Gliadels wafer was tested in two phase III clinical trials (11,12). The median survival time obtained in the treated patients was significantly prolonged in comparison to untreated patients, but the improvement was still limited since only a 2-month increase in survival time could be obtained.…”
Section: Introductionmentioning
confidence: 99%